Exploring Twitter for CSR Disclosure: Influence of CEO and Firm Characteristics in Latin American Companies - Suárez-Rico, Yuli Marcela; Gómez-Villegas, Mauricio; García-Benau, María Antonia (Sustainability, 2018)
Social networks, which are characterised by accessibility and interactivity, offer great potential for dialogue between companies and stakeholders, for example as platforms for publishing information on aspects of corporate social responsibility (CSR). In this paper, we use a synthetic index to analyse levels of CSR disclosure via Twitter, and identify explanatory variables of this disclosure by studying the demographic characteristics of the Chief Executive Officer (CEO) and of the company. This synthetic index was based on data for 93 companies located in the four countries of the Pacific Alliance (Chile, Colombia, Mexico, and Peru), using categories based on the 2016 Global Reporting Initave (GRI) Standards. The tweets were compiled during a period of two months in 2017, immediately before and after the publication of each CSR report. The synthetic index was taken as the dependent variable and used as the basis for multivariate regression analysis to identify the relationship between the level of CSR disclosure on Twitter and the characteristics of the firm and its CEO. The results obtained show that firms operating in environmentally-sensitive industries present higher levels of CSR disclosure on Twitter than those in other sectors. By country of origin, the Colombian and Chilean companies offered higher levels of disclosure than those in Mexico and Peru. The regression analysis revealed a positive relationship between the firm operating in a sensitive industry and its level of CSR disclosure on Twitter, and an inverse relationship between the latter variable and the tenure of the CEO.